The Study of Guidelines of Integrated Food Waste Management in Dusit Thani College - Junsuthonpoj, Sumeth; Roswarn, Visawat (Dusit Thani College Journal, 2022)
The purposes of this research were (1) to study the sources of food waste within the food supply chain of Dusit Thani College (DTC) (2) to analyze data on the quantity and characteristics of food waste in DTC, and (3) to develop an integrated food waste management model for DTC. This research used a structured interview form to conduct a focus group interview by categorizing the groups of people according to the food supply chain and used survey study to collect data and to analyze the rate of food waste, amount of food waste including surveys using questionnaires on food waste generation behavior and food waste management among those involved in the food supply chain. The research finding had led three conclusions. Firstly, the source of food waste from the food supply chain that occurred under DTC's operations will occur in stages of raw material storage, cooking and consumption both in kitchen practical classroom and in cafeteria. Secondly, Food waste generated can be divided into 3 types: avoidable, possibly avoidable and unavoidable food waste. The maximum amount of waste generated in the kitchen practical room was 125.2 kg, 5.21 kg and 61.25 kg respectively, while the maximum amount of waste generated in the cafeteria was 39.08 kg, 3.83 kg and 6.55 kg respectively. Finally, a intergated food waste management model throughout the college's operational supply chain includes the following stages: (1) prevention of food wasted at the sources (2) optimization and (3) recycle or composting food waste.